Mortality from infectious pneumonia in metal workers: a comparison with deaths from asthma in occupations exposed to respiratory sensitisers - Palmer, K. T.; Cullinan, P.; Rice, S.; Brown, T.; Coggon, D. (BMJ Publishing Group, 2009)
Background: National analyses of mortality in England and Wales have repeatedly shown excess deaths from pneumonia in welders. During 1979-90 the excess was attributable largely to deaths from lobar pneumonia and pneumonias other than bronchopneumonia, limited to men of working age and apparent in other occupations with exposure to metal fumes. The findings for 1991-2000 were assessed and compared with the mortality pattern from asthma in occupations exposed to known respiratory sensitisers. Methods: The Office of National Statistics supplied data on deaths by underlying cause among men aged 16-74 years in England and Wales during 1991-2000, including age and last held occupation. Data were abstracted on pneumonia for occupations with exposure to metal fumes and on asthma for occupations commonly reported to surveillance schemes as at risk of occupational asthma. The expected numbers of deaths were estimated by applying age-specific proportions of deaths by cause in the population to the total deaths by age in each occupational group. Observed and expected numbers were compared for each cause of death. Results: Among men of working age in occupations with exposure to metal fumes there was excess mortality from pneumococcal and lobar pneumonia (54 deaths vs 27.3 expected) and from pneumonias other than bronchopneumonia (71 vs 52.4), but no excess from these causes at older ages or from bronchopneumonia at any age. The attributable mortality from metal fume exposure was 45.3 excess deaths compared with an estimated 62.6 deaths from occupational asthma. Conclusion: Exposure to metal fumes is a material cause of occupational mortality. The hazard deserves far more attention than it presently receives.
Keywords: reported incidence fatal asthma diisocyanate subject